Applicability and tolerability of electrical stimulation applied to the upper and lower leg skin surface for cueing applications in Parkinson's disease. (January 2021) - Sweeney, Dean; Quinlan, Leo R.; Browne, Patrick; Counihan, Timothy; Rodriguez-Molinero, Alejandro; ÓLaighin, Gearóid
Highlights: Sensory electrical stimulation should be applicable & tolerable for cueing in PwP. Motor electrical stimulation should be applied with caution in PwP. Upper leg sites most suitable for sensory electrical stimulation cueing in PD. Abstract: Due to possible sensory impairments in people with Parkinson's disease, several methodological aspects of electrical stimulation as a potential cueing method remain to be explored. This study aimed to investigate the applicability and tolerability of sensory and motor electrical stimulation in 10 people with Parkinson's disease. The study focused on assessing the electrical stimulation voltages and visual analogue scale discomfort scores at the electrical sensory, motor, discomfort, and pain thresholds. Results show that sensory electrical stimulation at the tibialis anterior, soleus, hamstrings, and quadriceps stimulation sites was applicable and tolerable for 6/10, 10/10, 9/10, and 10/10 participants, respectively. Furthermore, motor electrical stimulation at the tibialis anterior, soleus, hamstrings, and quadriceps stimulation sites were applicable and tolerable for 7/10, 7/10, 7/10, and 8/10 participants, respectively. Interestingly, the thresholds for the lower leg were higher than those of the upper leg. The data presented in this paper indicate that sensory and motor electrical stimulation is applicable and tolerable for cueing applications in people with Parkinson's disease. Sensory electrical stimulation was applicable and tolerable at the soleus and quadriceps sites. Motor electrical stimulation was not tolerable for two participants at any of the proposed stimulation sites. Therefore, future studies investigating motor electrical stimulation cueing, should apply it with caution in people with Parkinson's disease.